Penggunaan Media Sosial Dalam Menentukan Perilaku Pelajar : (Sebuah Tinjaun Literatur) (International Forum of Researchers and Lecturers, 2024)
The development of technology and information is currently very rapid, almost all aspects of human needs have been affected and are instantaneous which are closely related to technology. The negative impact is that some students misuse social media as a tool to commit crimes, for example spreading hoax news, watching content that should not be watched, when given an assignment they prefer to do it using Google rather than having to search for literature that has been provided by the Government in the form of books available in the library. Meanwhile, the positive impact is that it makes it easier for students to manage accurate information. This type of research is a literature review, namely a survey of scientific articles, journals/proceedings, and other literature appropriate to a particular field of research or theory with the aim of obtaining a description and summary. Based on the literature review carried out, 9 articles were reviewed, there were 4 articles which stated that they agreed that the influence of using social media could have a bad impact on student behavior, and there were 5 articles which stated that the use of social media did not have a bad impact on student behavior.